Regioselective oxo-amination of alkenes and enol ethers with N-bromosuccinimide-dimethyl sulfoxide combination: a facile synthesis of alpha-amino-ketones and esters - Prasad, Pragati K.; Reddi, Rambabu N.; Sudalai, Arumugam (Organic Letters, 2016)
An unprecedented conversion of alkenes and enol ethers to the corresponding a-imido carbonyl compounds with excellent regioselectivity and yields has been developed. This oxo-amination process employs readily available N-bromosuccinimide (NBS) and secondary amines as N-sources and dimethyl sulfoxide (DMSO) as the oxidant and also leads to the production of amino alcohols in a single step on reduction, thus broadening the scope of this operationally simple reaction. For the first time, the formation of reactive Me2S+-O-Br species generated by the interaction of NBS with DMSO has been proven.